Cloning of the contiguous 165-kilobase-pair region around the terminus of Escherichia coli K-12 DNA replication. - Asada, K (1985)
Escherichia coli K-12 chromosomal DNA was partially digested with either EcoRI or HindIII, and cosmid libraries were constructed. By screening these libraries, a series of partially overlapping clones which covered the terC region was isolated. The cloned area spanned about 165 kilobase pairs, corresponding to the 29.7-to-33.2-min region of the genetic map of the E. coli chromosome.